The effect of strength training on 'handball goalie's elbow'--a prospective uncontrolled clinical trial - Tyrdal, S.; Pettersen, O. J. (Scandinavian Journal of Medicine & Science in Sports, 1998)
Handball goalie's elbow' is defined as pain due to repetitive forced hyperextension of the elbow. Strength training has been suggested for prevention and rehabilitation of this injury. The present study examines the effect of a strength-training programme after 24 months in a prospective uncontrolled clinical trial in goalkeepers with 'handball goalie's elbow'. Concentric and eccentric elbow exercise loads at approximately 80% of one repetition maximum (1-RM) were carried out 8 to 10 times 3 times a day, 3 days a week. Muscle strength was measured for flexion and extension of the elbow and wrist, and pro- and supination of the forearm. Sixteen amateur goalkeepers (10 men and 6 women) with 25 (12 right and 13 left) injured elbows (16 male and 9 female) were evaluated. Their mean age was 21.0 (range 16-35) years and their elbow pain had at the time of inclusion lasted for 28.9 (range 3-54) months. The players were tested at inclusion and after 24 months. The strength tests showed improvement in all the tested motions. The subjective status of the goalkeepers was excellent in 9, good in 9, and fair in 7. The study indicates that specific strength training may be effective in rehabilitation of 'handball goalie's elbow'.